PENINGKATAN PENGETAHUAN DAN KETERAMPILAN IBU DALAM MANAJEMEN LAKTASI DI DESA DUKO TAMBIH KECAMATAN TRAGAH BANGKALAN - Merlyna Suryaningsih; Qurrotu Aini (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
Exclusive breastfeeding is breastfeeding for newborns up to 6 months of age without being given additional food or other drinks including water, formula milk or other foods, except medicines and vitamins. One of the efforts to reduce infant and child morbidity and mortality, the United Nation Children's Fund (UNICEF) and the World Health Organization (WHO) recommend that breast milk (ASI) should be given to babies for at least six months without solid or mixed foods. Based on the results of the survey conducted, Posyandu in Dukoh Tambih Village have never been given lactation management training, one of which is exclusive breastfeeding counseling. Based on information from the midwife, there are still some babies aged 0-6 months who are still given breast milk and formula milk. Therefore it is necessary to make an effort to increase the awareness and knowledge of mothers in the village of Dukoh Tambih about lactation management. The method used in this community service is to collect data on mothers who have babies aged 0-24 months. Then do a time contract for 2 meetings. The first meeting is counseling about exclusive breastfeeding and the correct way of breastfeeding. Meanwhile, the second meeting was a demonstration of proper breastfeeding and breast care. During this activity, the participants were very enthusiastic about the material presented and during the demonstration. Some participants have also been able to demonstrate proper breastfeeding and breast care